Impact of Urban Heat Island on Daily Life of People in Bangkok Metropolitan Region (BMR) - Iamtrakul, Pawinee; Nusook, Tattep; Ubolchay, Ponjanat (Journal of Architectural/Planning Research and Studies (JARS), 2014)
The climate change have been obtained the much attention worldwide in order to launch the mitigation policy and implementation for alleviate this crisis. From the statistical data in 2013 found that an average temperature of Bangkok Metropolitan Region area was 36 degrees Celsius which is higher than an average temperature of suburban area around 3 degrees Celsius. This phenomenon is affecting to daily lives of humans’ which was influence by number of population, economics, and urban density. This study attempted to assess transportation behavior and daily life activity (electricity and energy consumption), including, an attitude on the advertising and law or regulation which promote energy consumption reduction. The cause of the improper behavior would be examined by exploring different area of Bangkok Metropolitan Region (suburban, center area, and central business district). This study conducted the 675 questionnaires survey for data collection and applying logistic regression analysis method is finding a relationship of the influencing factors. The result of study demonstrated that the public transport users have a positive attitude since a most of people agree by adopting public transportation as a main mode in daily transportation for energy reduction and reduction carbon dioxide emissions. Therefore, to mitigate the problematic of Urban Heat Island, the city should launch campaign to raise people awareness and motivation for change the individual behavior and attitudes on both travel pattern and daily activity. The approach would be an attractive to mitigate Urban Heat Island problem and reach to the livable.